Promoting SME development in Indonesia - Mourougane, Annabelle (OECD Economics Department Working Papers, 2012)
Micro, small and medium-sized firms (MSMEs) are a key source of employment and economic growth in Indonesia. They contributed to the country’s economic resilience during the 2008-09 financial crisis. But many suffer from low productivity, curbing their role in boosting living standards. There are several ways to spur MSME productivity growth over the medium term. The first route would be to encourage the formalisation of small firms. Lessening red tape through simplification of the licensing process and lower tax compliance costs would help. Avoiding excessive rises in the minimum wage in provinces where it is already at a reasonable level would also be important. Looking forward, it would be useful to remove rigidities in the formal labour markets, while moving to some form of unemployment benefit system to insure workers against job-loss risks. The second route would be to boost investment. Clarifying property rights for real estate, and making the information collected by the credit bureau available to all financial institutions would ease access to finance. At the same time, the development of financing alternatives such as venture capital, leasing or micro-finance would enhance credit supply. The poor state of infrastructure, in particular in the transportation and electricity sectors, is also perceived as an important impediment to investment and could be remedied by increasing public infrastructure spending on cost-effective projects. The third route would be to enhance the quality of human resources. The country suffers from a lack of skilled workers, and policies should aim both at increasing the pool of workers and making education and training institutions more responsive to evolving labour-market demand. Indonesia has a long tradition of supporting MSMEs. But responsibilities between the different levels of government and within the central government need to be clarified to minimise overlap and inefficiencies. A rigorous assessment of existing programmes would allow schemes to be consolidated and scarce public funds to be directed to their most cost-effective uses.
Number: 995 Publisher: OECD
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

The White Gold: The Role of Government and State in Rehabilitating the Sugar Industry in Mozambique - Buur, Lars; Mondlane Tembe, Carlota; Baloi, Obede (The Journal of Development Studies, 2012)
This article examines the rehabilitation of the sugar industry in Mozambique after the General Peace Accord in 1992, engaging primarily and critically with certain aspects of the business-state literature. It explains why the sugar sector was rehabilitated from the perspectives of Mozambican state, government and industry actors. The article argues that support for the industry cannot be identified in singular and one-dimensional terms, but must include a variety of attributes of support that emerged from a post-independence fusion of industry, state and government officials' historical experiences of success and failure in the industry, and pragmatic as well as longer-term ideological stances. This, it is argued, created a ‘mediating bureaucracy’ that could broker between the diverse interests and aspirations of state/government and industry.
Publisher: Routledge _eprint: https://doi.org/10.1080/00220388.2011.635200
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

A systematic review of collaboration and network research in the public affairs literature: implications for public health practice and research - Varda, Danielle; Shoup, Jo Ann; Miller, Sara (American journal of public health, 2012)
OBJECTIVES: We explored and analyzed how findings from public affairs research can inform public health research and practice, specifically in the area of interorganizational collaboration, one of the most promising practice-based approaches in the public health field. METHODS: We conducted a systematic review of the public affairs literature by following a grounded theory approach. We coded 151 articles for demographics and empirical findings (n = 258). RESULTS: Three primary findings stand out in the public affairs literature: network structure affects governance, management strategies exist for administrators, and collaboration can be linked to outcomes. These findings are linked to priorities in public health practice. CONCLUSIONS: Overall, we found that public affairs has a long and rich history of research in collaborations that offers unique organizational theory and management tools to public health practitioners.
Edition: 2011/11/28 Publisher: American Public Health Association
Keywords: L - english / inglês; collaboration / colaboração; health / saúde

Gender Disparity in Laws and Female Employment - Amin, Mohammad (Mimeograph, 2012)
Berkeley Electronic Press Selected Works, In a large sample of firms in 66 developing countries, it is shown that gender specific disparity in the laws favoring males over females tends to lower the employment of females relative to males at the firm level. However, this relationship between gender disparity in laws and employment is driven by small and medium firms, and it does not hold for the sample of large firms. However, the relationship holds equally in rich vs. poor countries, small vs. large cities within countries and among firms with and without female owners. We also confirm a sharp negative effect of gender disparity in the laws on the absolute level of employment of females. In short, in the presence of gender disparity in the laws, suitable reforms or policy measures promoting female employment may be required to achieve greater employment of women and greater gender parity in employment.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

From Negligence to Populism: An Analysis of Mozambique’s Agricultural Political Economy - Rosário, Domingos Manuel do (2012)
The paper analyses the changing configuration of the political system since the Rome Peace Agreement of 1992. It discusses how the “political settlement” underlying the Peace Agreement and the outcomes of multiparty elections thereafter have shaped governance, including policy-making concerning the agriculture sector and the rural economy. The paper argues that private interests and electoral objectives have been important drivers of policy decisions taken by the governing elites concerning the agriculture sector and local governance, with precedence over donor influence. By contrasting the political choices and governance approaches adopted by the two different presidential administrations in office since the first multiparty elections were held in 1994, it is argued that one (led by Joaquim Chissano) is marked by features of “neopatrimonialism”, whereas the other (led by Armando Guebuza) is showing signs of electoral “populism”. The former is characterised by significant rent distribution by the governing elite to a narrow “selectorate”. The latter is manifested by a paternalistic and politically mobilising discourse emanating directly from the President and appealing to the broader electorate, particularly the rural population of the central and Northern region of the country, who has been traditionally opposed to the ruling party
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura